Catalyst for synthesizing N-methylaniline by gas phase method, preparation method and application thereof
Through a multi-step reaction method, zinc, manganese and copper salts are impregnated on the metal oxide support, and trimethylol acid is added to form highly dispersed copper nanoparticles, solving the problem of poor catalyst activity and stability, and realizing the synthesis of N- by gas phase method The efficiency and stability of methylaniline catalysts are improved.
Patent Information
- Application Number
- CN202411440834.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing gas-phase method of synthesis of N-methylaniline catalysts has problems such as poor catalyst activity, low selectivity and poor stability, especially poor catalyst resistance and thermal stability, resulting in poor catalytic performance.
The zinc salt, manganese salt and copper salt are impregnated onto the metal oxide support by using a multi-step reaction method, and trimethylol acid is added in the subsequent steps, and zinc oxide is made by etching and coordination complexing by organic acid. Redisperse with manganese oxide to form Cu3 (BTC)2 structure, forming highly dispersed copper nanoparticles. The carbon layer on the copper surface inhibits poisoning and sintering, and improves the stability of the catalyst.
High activity and selectivity of the catalyst are achieved, while improving the stability of the catalyst, and can maintain efficient catalytic efficiency for a long time without the need for hydrogen activation and pretreatment.
Smart Images

Figure CN118950024B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts containing metal oxides, and in particular relates to a catalyst prepared by loading multiple metals onto a metal oxide carrier through multi-step reactions. The catalyst can be used for synthesizing N-methylaniline by a gas phase method. Background Art
[0002] N-methylaniline (NMA for short) is an important chemical raw material. It is widely used in the production of pesticides, medicines, dyes, rubber, etc. In addition, N-methylaniline can also be used as a gasoline antiknock agent, acid absorbent, solvent and explosive stabilizer, etc. It is also a potential ligand in organometallic chemistry and catalytic processes.
[0003] There are two main synthetic processes for N-methylaniline: liquid phase method and gas phase method. In the liquid phase method, inorganic acids such as phosphoric acid or sulfuric acid are usually used as catalysts, and the reaction process is carried out with the help of batch reactors. This method has some significant disadvantages, including the need for frequent operation, relatively low production efficiency, strong corrosion to equipment, resulting in cumbersome post-processing work, and possible environmental pollution problems. In contrast, the gas phase method provides a more environmentally friendly and efficient alternative. The gas phase method is a method for producing NMA by gas phase reaction in a fixed bed reactor under normal pressure conditions using aniline and methanol as the main raw materials. This method uses a solid acid catalyst, which effectively avoids the various disadvantages brought by the liquid phase method. It not only realizes the continuous production of NMA, but also has significant advantages such as low process equipment investment cost, simple operation, no equipment corrosion problems, and environmental friendliness. However, the gas phase method also has problems such as poor catalyst activity, low selectivity, and poor stability.
[0004] Patent (CN 201710299685.8) reported a copper-zinc-chromium-aluminum spinel catalyst, which does not require hydrogenation reduction pretreatment before use, and the single-pass conversion rate of aniline is over 90%, and the selectivity of N-methylaniline is over 98%. Patent (CN202311121721.3) discloses a copper-zinc-chromium catalyst for the synthesis of N-methylaniline, which needs to be activated by methanol water vapor before use. Patent (CN 201310004072.9) reported a chromium-free catalyst for the gas phase synthesis of N-methylaniline; the catalyst contains 30% to 70% copper, 10% to 50% zinc, 5% to 20% alkaline earth metals, and 0.2% to 2% rare earth elements cerium or lanthanum by weight (in terms of oxides). Wang Di et al. (Contemporary Chemical Industry, 2017, 46(1), 157-159) prepared a series of CuO / ZnO / Al2O3 catalysts for the synthesis of N-methylaniline by co-precipitation method and found that the catalytic performance was affected by the preparation conditions and additives. To date, the active center, synergistic reaction mechanism, deactivation and poisoning mechanism of this type of catalyst are still unclear. In the actual catalyst evaluation process, we found that although these catalysts have high initial activity, their stability is not ideal. The reason is that the catalysts have poor anti-toxicity and thermal stability. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a catalyst for synthesizing N-methylaniline by a gas phase method, and a preparation method and application thereof.
[0006] The technical solution adopted by the present invention is: a method for preparing a catalyst for synthesizing N-methylaniline by a gas phase method, comprising the following steps:
[0007] Step 1: impregnate the mixed solution containing zinc salt and manganese salt into the metal oxide support by equal volume impregnation method, dry after standing, and calcine in air atmosphere to obtain sample A;
[0008] Step 2: Impregnate an equal volume of the solution containing copper salt into sample A, let it stand and then dry to obtain sample B;
[0009] Step 3: impregnate the solution containing trimesic acid into sample B by double volume impregnation method, stir, and dry to obtain sample D;
[0010] Step 4: Heat-treat sample D in an air atmosphere, and then switch to an inert atmosphere for calcination to obtain a catalyst for gas-phase synthesis of N-methylaniline.
[0011] Preferably, the molar ratio of trimesic acid to copper salt is 1-2:1.
[0012] Preferably, the zinc salt is zinc nitrate, the manganese salt is manganese nitrate, and the copper salt is copper nitrate, and the mass of copper nitrate accounts for 5%-20% of the mass of sample A; in step 1, the mass ratio of zinc nitrate to manganese nitrate is 1:1, and the mass of zinc nitrate and manganese nitrate accounts for 5%-20% of the mass of the metal oxide carrier.
[0013] Preferably, in step 4, the heat treatment temperature is 250-350° C., and the heat treatment time is 1-3 h.
[0014] Preferably, in step 1, step 2 and step 3, the drying temperature is 60-80°C.
[0015] Preferably, in step one, the calcination temperature is 500-550°C; in step four, the calcination temperature is 500-600°C.
[0016] Preferably, the metal oxide support is a mixture of one or more of alumina, silica, zirconia, ceria and titania.
[0017] The catalyst is prepared by the method for preparing a catalyst for synthesizing N-methylaniline by a gas phase method.
[0018] Application of catalyst in gas phase synthesis of N-methylaniline.
[0019] Preferably, the method is applied to synthesizing N-methylaniline from aniline and methanol by a gas phase method in a fixed bed reactor at atmospheric pressure, and the specific steps are as follows:
[0020] The catalyst was loaded into the constant temperature range of a continuous flow atmospheric pressure fixed bed reactor, and a ceramic ring was loaded on the catalyst as a preheating layer. The temperature was raised to 180-200 °C in a flowing nitrogen atmosphere for pretreatment for at least 1 h.
[0021] The nitrogen was turned off and a mixed solution of methanol and aniline with a molar ratio of 1.5–2.0:1 was pumped into the reactor through a pressure pump, where the liquid hourly space velocity of the mixed solution was 0.1–1.0 h –1 ;
[0022] After the products are collected by condensation, gas chromatography is used to conduct qualitative and quantitative analysis on the products after the reaction;
[0023] After the reaction is completed, stop feeding first, then continue purging with nitrogen for at least 1 h, then cool down, and turn off the nitrogen after the temperature drops below 100 °C.
[0024] The advantages and positive effects of the present invention are as follows: a green chromium-free catalyst is provided, trimesic acid is added during the preparation process, and the organic acid etching and coordination complexing effects of trimesic acid are utilized to enable zinc oxide and manganese oxide to be better redispersed on a metal oxide carrier; at the same time, trimesic acid reacts with copper ions to generate a Cu3(BTC)2 structure, which can obtain highly dispersed carbon-confined copper nanoparticles during subsequent heat treatment and calcination processes; the carbon layer on the copper surface can inhibit poisoning and sintering of the copper nanoparticles, and further improve the stability of the catalyst while ensuring high activity and selectivity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Scanning electron microscope image of the catalyst prepared in Example 1. DETAILED DESCRIPTION
[0026] The embodiments of the present invention are described below with reference to the accompanying drawings.
[0027] The present invention relates to a catalyst for synthesizing N-methylaniline by a gas phase method and a preparation method thereof, and provides a green chromium-free catalyst, which further improves the stability of the catalyst under the premise of ensuring high activity and selectivity of the catalyst. The catalyst uses metal oxide as a carrier, is loaded with copper, zinc and manganese, is added with trimesic acid during the preparation process, and utilizes the organic acid etching and coordination complexation of trimesic acid to enable zinc oxide and manganese oxide to be better redispersed on the metal oxide carrier; at the same time, trimesic acid reacts with copper ions to generate a Cu3(BTC)2 structure, which can obtain highly dispersed carbon-confined copper nanoparticles in subsequent heat treatment and roasting processes. The carbon layer on the copper surface can inhibit poisoning and sintering of copper nanoparticles, thereby playing a role in improving the activity and stability of the catalyst.
[0028] The specific preparation method of the catalyst for synthesizing N-methylaniline by gas phase method is as follows:
[0029] Step 1: Under stirring at room temperature, zinc nitrate and manganese nitrate are dissolved in deionized water to obtain a mixed solution, the mass ratio of zinc nitrate to manganese nitrate is 1:1, and then they are impregnated into a metal oxide carrier by an equal volume impregnation method, the mass of zinc nitrate and manganese nitrate accounts for 5%-20% of the mass of the metal oxide carrier, and the sample is sealed and left to stand for at least 3 hours, and then thoroughly dried at 60-80 ° C, and then the sample is calcined at 500-550 ° C in an air atmosphere for at least 2 hours to obtain sample A; wherein the metal oxide carrier is a mixture of one or more of aluminum oxide, silicon oxide, zirconium oxide, cerium oxide, and titanium oxide;
[0030] Step 2: Under stirring at room temperature, dissolve copper nitrate in deionized water to obtain a copper nitrate solution, and then impregnate it into sample A using an equal volume impregnation method, with the mass of copper nitrate accounting for 5%-20% of the mass of sample A. After sealing and standing for at least 3 hours, thoroughly dry at 60-80 °C to obtain sample B;
[0031] Step 3: Under stirring at room temperature, dissolve trimesic acid in methanol to obtain solution C, then use the double volume impregnation method to impregnate solution C into sample B, continue stirring for at least 12 hours after sealing, then filter and separate the obtained sample, and then thoroughly dry it at 60-80 °C to obtain sample D; wherein the molar ratio of trimesic acid to copper nitrate is 1-2:1;
[0032] Step 4: Place sample D in a tube furnace and heat it to 250–350 °C for 1–3 h in a flowing air atmosphere. Then switch to a flowing inert atmosphere and continue heating to 500–600 °C for calcination for at least 3 h. Then cool it down to room temperature to obtain the desired catalyst. During the heat treatment or calcination process, the gas volume space velocity is 40–80 h –1 .
[0033] Among them, in step 1, after zinc nitrate and manganese nitrate are loaded on the metal oxide carrier, they need to be converted into a mixture of zinc oxide and manganese oxide by roasting in air. In step 2, copper nitrate is only dried after loading to keep the ionic state of copper salt, so that in the subsequent step 3, trimesic acid is preferentially complexed with copper ions to form a metal organic framework material Cu3(BTC)2 structure, and highly dispersed carbon-confined copper nanoparticles can be obtained in the subsequent heat treatment and roasting process; then, excess trimesic acid continues to react with zinc oxide and manganese oxide, which will cause the zinc oxide and manganese oxide particles to be etched, and better redispersion can be achieved through subsequent roasting and other steps. The molar ratio of trimesic acid to copper nitrate is 1-2:1, which can ensure that there is enough trimesic acid to react with copper ions to form Cu3(BTC)2 structure, and there is also remaining trimesic acid to continue to react with zinc oxide and manganese oxide nanoparticles. In addition, the amount of trimesic acid should not be too much, otherwise the carbon content in the catalyst is too high, which will bury the active center of the catalyst.
[0034] In step 4, the calcination process of sample D needs to first be heated to 250-350 °C for 1-3 h in a flowing air atmosphere, in order to introduce oxygen, reduce the content of carbon species, and avoid excessive carbon species from burying the active center; then switch to a flowing inert atmosphere and continue to heat up to 500-600 °C for calcination for at least 3 h, in order to further decompose the carbon species and reduce the copper to a metal element; the catalyst prepared in this way does not require hydrogen activation and pretreatment during use.
[0035] The catalyst prepared by the above method can be used for gas phase synthesis of N-methylaniline. Specifically, the catalyst is mainly used for gas phase synthesis of N-methylaniline from aniline and methanol in a fixed bed reactor at normal pressure, and the specific preparation process is as follows:
[0036] Step 1: Load the catalyst into the constant temperature range of a continuous flow atmospheric pressure fixed bed reactor, and load a ceramic ring of at least 20 cm on the catalyst as a preheating layer, and heat to 180-200 °C in a flowing nitrogen atmosphere for pretreatment for at least 1 hour;
[0037] Step 2: Turn off the nitrogen and pump a mixed solution of methanol and aniline with a molar ratio of 1.5–2.0:1 into the reactor through a pressure pump, where the liquid hourly space velocity of the mixed solution is 0.1–1.0 h –1 ;
[0038] Step 3: After collecting the product by condensation, the product after the reaction is qualitatively and quantitatively analyzed by gas chromatography;
[0039] Step 4: After the reaction is completed, stop feeding first, then continue purging with nitrogen for at least 1 h, then cool down, and turn off the nitrogen after the temperature drops below 100 °C.
[0040] Experimental verification shows that the catalyst prepared by the method of the present invention exhibits better catalytic activity and stability in the reaction of synthesizing N-methylaniline by the gas phase method.
[0041] The scheme of the present invention is described below in conjunction with the accompanying drawings, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.
[0042] Example 1
[0043] (1) Under stirring at room temperature, zinc nitrate and manganese nitrate were dissolved in deionized water to obtain a mixed solution, which was then impregnated into a silica carrier by an equal volume impregnation method. The solution was sealed and allowed to stand for 3 h and then thoroughly dried at 80 °C. The sample was then calcined at 500 °C in an air atmosphere for 2 h to obtain sample A, wherein the mass of zinc nitrate and manganese nitrate accounted for 20% of the mass of the silica carrier; and the mass ratio of zinc nitrate to manganese nitrate was 1:1.
[0044] (2) Under stirring at room temperature, copper nitrate was dissolved in deionized water to obtain a copper nitrate solution, which was then impregnated into sample A using an equal volume impregnation method. The solution was sealed and allowed to stand for 3 h and then thoroughly dried at 80 °C to obtain sample B; the mass of copper nitrate accounted for 20% of the mass of sample A.
[0045] (3) Under stirring at room temperature, trimesic acid was dissolved in methanol to obtain solution C, and then solution C was impregnated into sample B using the double volume impregnation method. After sealing, stirring was continued for 12 h. The obtained sample was then filtered and separated, and then thoroughly dried at 80 °C to obtain sample D; wherein the molar ratio of trimesic acid to copper nitrate was 2:1.
[0046] (4) Sample D was placed in a tubular furnace and heated to 250 °C for 3 h in a flowing air atmosphere. Then, the temperature was switched to a flowing inert atmosphere and the temperature was further raised to 600 °C for calcination for 3 h. The temperature was then cooled to room temperature to obtain the desired catalyst. The gas volume space velocity was 40 h / min. –1 The obtained catalyst is numbered CAT-1.
[0047] The prepared catalyst CAT-1 was tested, and its scanning electron microscope image is as follows: Figure 1 As shown, a regular polyhedral morphology structure can be seen.
[0048] Example 2
[0049] The preparation steps of Example 2 are the same as those of Example 1, except that the silicon oxide carrier in step (1) is replaced by an aluminum oxide carrier. The resulting catalyst is numbered CAT-2.
[0050] Example 3
[0051] The preparation steps of Example 3 are the same as those of Example 1, except that the mass of zinc nitrate and manganese nitrate in step (1) is changed from 20% to 5% of the mass of the silica carrier. The resulting catalyst is numbered CAT-3.
[0052] Example 4
[0053] The preparation steps of Example 4 are the same as those of Example 1, except that the mass of copper nitrate in step (2) is changed from 20% to 5% of the mass of sample A. The resulting catalyst is numbered CAT-4.
[0054] Example 5
[0055] The preparation steps of Example 5 are the same as those of Example 1, except that the molar ratio of trimesic acid to copper nitrate in step (3) is changed from 2:1 to 1:1. The obtained catalyst is numbered CAT-5.
[0056] Comparative Example 1
[0057] The purpose is to compare with Example 1 to illustrate the effect of calcination at 500°C for 2 h in air atmosphere in step (1) on the catalyst.
[0058] The preparation steps of Comparative Example 1 are the same as those of Example 1, except that the step (1) of calcining the sample at 500° C. in an air atmosphere for 2 h is removed; the obtained catalyst is numbered CAT-6.
[0059] Comparative Example 2
[0060] The purpose is to compare with Example 1 to illustrate the effect of the existence form of copper species on the catalyst.
[0061] The preparation steps of Comparative Example 2 are the same as those of Example 1, except that the sample dried in step (2) is calcined again at 500° C. for 2 h in an air atmosphere; the obtained catalyst is numbered CAT-7.
[0062] Comparative Example 3
[0063] The purpose is to make a comparison with Example 1 to illustrate the effect of the amount of trimesic acid on the catalyst.
[0064] The preparation steps of Comparative Example 3 are the same as those of Example 1, except that the molar ratio of trimesic acid to copper nitrate in step (3) is changed from 2:1 to 0.5:1; the obtained catalyst is numbered CAT-8.
[0065] Comparative Example 4
[0066] The purpose is to make a comparison with Example 1 to illustrate the effect of the amount of trimesic acid on the catalyst.
[0067] The preparation steps of Comparative Example 4 are the same as those of Example 1, except that the molar ratio of trimesic acid to copper nitrate in step (3) is changed from 2:1 to 2.5:1; the obtained catalyst is numbered CAT-9.
[0068] Comparative Example 5
[0069] The purpose is to make a comparison with Example 1 to illustrate the effect of low temperature heat treatment in air atmosphere on the catalyst.
[0070] The preparation steps of Comparative Example 5 are the same as those of Example 1, except that the step (4) in which the sample D is heated to 250° C. for 3 h under a flowing air atmosphere is omitted; the resulting catalyst is numbered CAT-10.
[0071] Comparative Example 6
[0072] The purpose is to make a comparison with Example 1 to illustrate the effect of high temperature calcination under an inert atmosphere on the catalyst.
[0073] The preparation steps of Comparative Example 6 are the same as those of Example 1, except that the step (4) in which the temperature of sample D is raised to 600° C. and calcined for 3 h under a flowing inert atmosphere is removed; the obtained catalyst is numbered CAT-11.
[0074] Example 6: Catalyst Activity Test
[0075] The test method is as follows:
[0076] (1) 20 mL of catalyst was loaded into the constant temperature range of a continuous flow atmospheric pressure fixed bed reactor, and a 20 cm ceramic ring was loaded on the catalyst as a preheating layer. The temperature was raised to 200 °C for pretreatment for 1 h under a flowing nitrogen atmosphere.
[0077] (2) Turn off the nitrogen gas and pump a mixed solution of methanol and aniline with a molar ratio of 2.0:1 into the reactor through a pressure pump. The liquid hourly space velocity of the mixed solution is 0.3 h –1 ;
[0078] (3) After collecting the products by condensation, the products are qualitatively and quantitatively analyzed by gas chromatography;
[0079] (4) After the reaction is completed, stop feeding first, then continue purging with nitrogen for 1 h, then cool down, and turn off the nitrogen after the temperature drops below 100°C.
[0080] The catalysts prepared in Examples 1-5 and Comparative Examples 1-6 were tested for their activities by the above test method. The results of the decrease rate of aniline conversion per unit time, the average conversion rate of aniline, and the average selectivity of N-methylaniline for different catalysts in the reaction period of 5-10 h are shown in Table 1.
[0081] Table 1
[0082]
[0083] According to the data in Table 1, the catalysts prepared in Examples 1-5 have a high aniline conversion rate, a higher N-methylaniline selectivity, and a very small change in the rate of decrease of aniline conversion within the reaction process of 5-10h, proving that the catalyst prepared by the method of the present invention has better stability, can maintain high catalytic efficiency for a long time, and has better selectivity. Compared with the catalysts in the examples, the catalysts in the comparative examples have differences in catalyst structure due to changes made at different angles during the preparation process, and the corresponding performance will also be affected. The comparative examples are affected to varying degrees in activity, selectivity, and stability.
[0084] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a catalyst for synthesizing N-methylaniline by a gas phase process, characterized in that: The steps include: Step 1: impregnate the mixed solution containing zinc salt and manganese salt into the metal oxide support by equal volume impregnation method, dry after standing, and calcine in air atmosphere to obtain sample A; Step 2: Impregnate an equal volume of the solution containing copper salt into sample A, let it stand and then dry to obtain sample B; Step 3: impregnate the solution containing trimesic acid into sample B by double volume impregnation method, stir, and dry to obtain sample D; Step 4: Heat-treat sample D in an air atmosphere, and then switch to an inert atmosphere for calcination to obtain a catalyst for gas-phase synthesis of N-methylaniline.
2. The method for preparing a catalyst for synthesizing N-methylaniline by a vapor phase method according to claim 1, characterized in that: The molar ratio of trimesic acid to copper salt is 1–2:
1.
3. The method for preparing a catalyst for synthesizing N-methylaniline by a vapor phase method according to claim 2, characterized in that: The zinc salt is zinc nitrate, the manganese salt is manganese nitrate, and the copper salt is copper nitrate, and the mass of copper nitrate accounts for 5%-20% of the mass of sample A; in step 1, the mass ratio of zinc nitrate to manganese nitrate is 1:1, and the mass of zinc nitrate and manganese nitrate accounts for 5%-20% of the mass of the metal oxide carrier.
4. The method for preparing a catalyst for synthesizing N-methylaniline by a vapor phase method according to claim 2, characterized in that: In step 4, the heat treatment temperature is 250-350°C, and the heat treatment time is 1-3h.
5. The method for preparing a catalyst for synthesizing N-methylaniline by a gas phase method according to claim 4, characterized in that: In step 1, step 2 and step 3, the drying temperature is 60-80°C.
6. The method for preparing a catalyst for synthesizing N-methylaniline by a gas phase method according to claim 4, characterized in that: In step 1, the calcination temperature is 500-550°C; in step 4, the calcination temperature is 500-600°C.
7. The method for preparing a catalyst for synthesizing N-methylaniline by a vapor phase method according to claim 1, characterized in that: The metal oxide support is a mixture of one or more of alumina, silica, zirconia, ceria and titania.
8. The catalyst prepared by the catalyst preparation method for synthesizing N-methylaniline by a vapor phase process according to any one of claims 1 to 7.
9. Use of the catalyst according to claim 8 in the gas phase synthesis of N-methylaniline.
10. Use of the catalyst according to claim 9 in the gas phase synthesis of N-methylaniline, characterized in that: It is applied to the gas phase synthesis of N-methylaniline from aniline and methanol in a fixed bed reactor at atmospheric pressure. The specific steps are as follows: The catalyst was loaded into the constant temperature range of a continuous flow atmospheric pressure fixed bed reactor, and a ceramic ring was loaded on the catalyst as a preheating layer. The temperature was raised to 180-200 °C in a flowing nitrogen atmosphere for pretreatment for at least 1 h. The nitrogen was turned off and a mixed solution of methanol and aniline with a molar ratio of 1.5–2.0:1 was pumped into the reactor through a pressure pump, where the liquid hourly space velocity of the mixed solution was 0.1–1.0 h –1 ; After the products are collected by condensation, gas chromatography is used to conduct qualitative and quantitative analysis on the products after the reaction; After the reaction is completed, stop feeding first, then continue purging with nitrogen for at least 1 h, then cool down, and turn off the nitrogen after the temperature drops below 100 °C.
Citation Information
Patent Citations
Novel N-methyl aniline catalyst synthesized through chromium-free gas phase method
CN103028411A
Preparation method of catalyst for synthesis of N-methylaniline and application
CN107115881A
Preparation method and application of copper-zinc-chromium catalyst for synthesizing N-methylaniline and N, N-dimethylaniline
CN117244554A
Treatment method for flue gas denitrification by catalysis of carbon-based metal organic framework type oxide
CN106215692A
Copper / silicon catalyst based on metal organic framework as well as preparation and application thereof
CN109772321A
